Aspects of library development planning, de J. Stephen Parker - Borges, Maria Alice Guimarães (Revista de Biblioteconomia de Brasília, 1983)
PARKER, J. Stephen. Aspects of library deveiopment planning. London: Mansel, 1983. 289p.